Efficacy of a theoretical‑practical course for the ultrasound measurement of the optic nerve diameter in different healthcare operators - Garofalo, Eugenio; Neri, Giuseppe; Bosco, Vincenzo; Caroleo, Zaninni; Virdò, Fabiola; Mastrangelo, Helenia; Guzzi, Giusy; Cammarota, Gianmaria; Robba, Chiara; Longhini, Federico; Bruni, Andrea; ONSD study group (The Ultrasound Journal, 2025)
Background: The measurement of the optic nerve sheath diameter (ONSD) via ultrasound is a non-invasive technique to estimate intracranial pressure. Brief training has been shown to be effective in accurately teaching the ONSD technique in specialized healthcare providers. This study evaluates the ability of medical and nursing students, Intensive Care Unit (ICU) nurses, and ICU residents to perform ONSD measurements after a brief training. Methods: Forty participants underwent a 4-h training session consisting of 30 min of lecture focusing on the key principles of the technique for ONSD measurement, followed by at least 20 measurements with an expert tutor. Thereafter, all participants assessed 5 ONSD measurements on healthy volunteers and their assessments were compared to those by the expert tutor. Results: All participants successfully visualized the optic nerve and recorded similar values among groups (p > 0.05 for all comparisons). ICU nurse residents and medical students demonstrated a good accuracyof measurements, as defined by an upper and lower limits of agreement with the expert tutor not exceeding 0.5 mm in the Bland–Altman analysis. On the opposite, nurse students had the highest error rates and poor accuracy in ONSD assessment. Conclusions: These findings highlight the feasibility of training medical students, ICU nurses and residents in ONSD measurement, opening the possibility of a wider application of this technique. After dedicated training, ONSD assessment and monitoring could be performed not only by specialists but also by other healthcare providers, including specialized nurses. This may serve as an additional tool for the rapid triage of patients, even in out-of-hospital settings.